Book Reviews (Blackfriars, 1932)
BOOK REVIEWS in this articles: Cinema Quarterly. Vol. 1, No. 1. Esprit. Revue Internationale. Edition Française. Octobre, 1932. First year, first number. Jasus And His Apostles. By Felix Klein. Translated by W. P. Baines. With a prefatory letter by H.E. Cardinal Verdier. If We Want Peace. By H. N. Brailsford. La Pedagogie Scolaire En Russie Sovietique. By Eugène Devaud. Casus Conscientiae. Propositi ac Soluti ab Eduardo Géicot, S.J. Edited by J. Salsmans, S.J. De Bonis Ecclesiae Temporalibus. By Marius Pistocchi. Gregoire And The French Revolution. By Lord Ashbourne. Apostolic Christianity, or The Witness of the Apostles to Christ. By the Rev. O. R. Vassall-Phillips, C.SS.R. Broadcast Minds. By Ronald A. Knox. (Sheed & Ward; PP. 275; 7/6.) Crumplin'. By Mary Sturge Gretton Pageant Of Life. A Human Drama. By Owen Francis Dudley. Tudor Sunset. By Mrs. Wilfrid Ward. Cinema Quarterly. Vol. I, No. I. Esprit. Revue Internationale. Edition Française. Octobre, 1932. First year, first number. Jesus and His Apostles. By Felix Klein. Translated by W. P. Baines. With a prefatory letter by H.E. Cardinal Verdier. If We Want Peace. By H. N. Brailsford. La Pedagogie Scolaire en Russie Sovietique. By Eugène Devaud. Casus Conscientiae. Propositi ac Soluti ab Eduardo Gènicot, S.J. Edited by J. Salsmans, S.J. De Bonis Ecclesiae Temporalibus. By Marius Pistocchi. Gregoire and the Franch Revolution. By Lord Ashbourne. Apostolic Christianity, or The Witness of the Apostles to Christ. By the Rev. O. R. Vassall-Phillips, C.SS.R. Broadcast Minds. By Ronald A. Knox. Crumplin'. By Mary Sturge Gretton Pageant of Life. A Human Drama. By Owen Francis Dudley. Trdor Sunset. By Mrs. Wilfrid Ward. Mimes, Sacred and Profane. By H. D. C. Pepler. The Four Minstrels of Bremen. By H.D.C.P. Missions and Missionaries. By Georges Goyau. The Things that are not Caesar's. By Jacques Maritain. (5/-) A Newman Synthesis. By Erich Przywara, S.J. St. Francis and the Blessed Eucharist. By Fr. Augustine, O.M.Cap. Mystical Studies in the Apocalypse. By the Rev. H. Erskine Hill. Vita Christi. Meditations on Our Lord's Public Life for the time after Pentecost. By Mother St. Paul, Religious of the Retreat of the Sacred Heart. Of Familir Intercourse with God in Prayer. By the Ven. Louis de Ponte, S.J. (From the ‘Spiritual Guide’ Translated by a Religious of the Order of St. Benedict. With an Introduction by the Most Rev. Alban Goodier, S.J. (Archbishop of Hierapolis). The Virtue of Trust. Meditations by Paul de Jaegher, S.J.